Development of juvenile sprint performance in boys: analysis of speed phases - a cross-sectional study by age - Bleeker, S.; Siener, M. (Frontiers in Sports and Active Living, 2025)
Introduction: Sprinting performance in youth is typically assessed using fixed distances, although sprinting consists of distinct phases that develop differently across age. Little is known about how acceleration, maximum velocity (Vmax), and deceleration phases change during growth. This study aimed to analyze sprint phase distribution in boys aged 12-19 years and to develop practical models for estimating key sprint parameters when advanced measurement systems are unavailable.